A Stable N‐Heterocyclic Silylene with a 1, 1′‐Ferrocenediyl Backbone. Issue 5 (1st December 2020) - Weyer, Nadine; Heinz, Myron; Schweizer, Julia I.; Bruhn, Clemens; Holthausen, Max C.; Siemeling, Ulrich
Abstract: The N‐heterocyclic silylene [{Fe(η 5 ‐C5 H4 ‐NDipp)2 }Si] (1DippSi, Dipp=2, 6‐diisopropylphenyl) shows an excellent combination of pronounced thermal stability and high reactivity towards small molecules. It reacts readily with CO2 and N2 O, respectively affording (1DippSi O2 )2 C and (1DippSi O)2 as follow‐up products of the silanone 1DippSi O. Its reactions with H2 O, NH3, and FcPH2 (Fc=ferrocenyl) furnish the respective oxidative addition products 1DippSi (H)X (X=OH, NH2, PHFc). Its reaction with H3 BNH3 unexpectedly results in B−H, instead of N−H, bond activation, affording 1DippSi (H)(BH2 NH3 ). DFT results suggest that dramatically different mechanisms are operative for these H−X insertions. Abstract : A stable cyclic diaminosilylene featuring a ferrocene‐based backbone is reported. The dicoordinate Si II atom is part of a six‐membered FeC2 N2 Si ring and shows a comparatively large bond angle of ca. 107°. This N‐heterocyclic silylene can activate strong bonds (C=O, N=O, B−H, N−H, P−H, O−H) under ambient conditions.